Association of High‐Density Lipoprotein‐Cholesterol Versus Apolipoprotein A‐I With Risk of Coronary Heart Disease: The European Prospective Investigation Into Cancer‐Norfolk Prospective Population Study, the Atherosclerosis Risk in Communities Study, and the Women's Health Study. Issue 8 (3rd August 2017) - van Capelleveen, Julian C.; Bochem, Andrea E.; Boekholdt, S. Matthijs; Mora, Samia; Hoogeveen, Ron C.; Ballantyne, Christie M.; Ridker, Paul M; Sun, Wensheng; Barter, Philip J.; Tall, Alan R.; Zwinderman, Aeilko H.; Kastelein, John J. P.; et al.
Abstract : Background: The contribution of apolipoprotein A‐I (apoA‐I) to coronary heart disease (CHD) risk stratification over and above high‐density lipoprotein cholesterol (HDL‐C) is unclear. We studied the associations between plasma levels of HDL‐C and apoA‐I, either alone or combined, with risk of CHD events and cardiovascular risk factors among apparently healthy men and women. Methods and Results: HDL‐C and apoA‐I levels were measured among 17 661 participants of the EPIC (European Prospective Investigation into Cancer)‐Norfolk prospective population study. Hazard ratios for CHD events and distributions of risk factors were calculated by quartiles of HDL‐C and apoA‐I. Results were validated using data from the ARIC (Atherosclerosis Risk in Communities) and WHS (Women's Health Study) cohorts, comprising 15 494 and 27 552 individuals, respectively. In EPIC‐Norfolk, both HDL‐C and apoA‐I quartiles were strongly and inversely associated with CHD risk. Within HDL‐C quartiles, higher apoA‐I levels were not associated with lower CHD risk; in fact, CHD risk was higher within some HDL‐C quartiles. ApoA‐I levels were associated with higher levels of CHD risk factors: higher body mass index, HbA1c, non‐HDL‐C, triglycerides, apolipoprotein B, systolic blood pressure, and C‐reactive protein, within fixed HDL‐C quartiles. In contrast, HDL‐C levels were consistently inversely associated with overall CHD risk and CHD risk factors within apoA‐I quartiles ( P <0.001). These findings were validated in the ARIC and WHS cohorts. Conclusions: Our findings demonstrate that apoA‐I levels do not offer predictive information over and above HDL‐C. In fact, within some HDL‐C quartiles, higher apoA‐I levels were associated with higher risk of CHD events, possibly because of the unexpected higher prevalence of cardiovascular risk factors in association with higher apoA‐I levels. Clinical Trial Registration: URL:https://www.clinicaltrials.gov . Unique identifier: NCT00000479.